The participatory recovery of history and memory for the social use of the cultural heritage of Huarochiri: The case of the former School N°443 - Pajuelo Montes, Rosario (2016)
The participatory process of the recovery of the history and memory related to the former Nº 443 school brings critical social research and dialogical practices forward. This allows the construction of knowledge based in the wisdom, language and the way of understanding of the local population. It also leads to the inclusion of social sciences, arts and ancestral wisdom. In the participatory process of recovery, the local voices were decisive in the selection of the object of study; in the recognition of the economic, political, social cultural and territorial issues; and in the identification of the interests, needs and expectations that will define the social use of the edification. School 443 shows facts, knowledge and experiences of the past visible that were constructed and enriched by the communitarian ties. As well, it is the material expression and territorial referent of experiences that still persist, and will keep alive the tradition, memory and identity that preserve cultural heritage and improve the quality of life of the Huarochiri population.